ANNOTATED BIBLIOGRAPHY OF WORKS OF DR VOJISLAV DANCETOVIC (Heritage, 2025)
This work presents an annotated bibliography of the works of Vojislav Dančetović, an exceptional expert in the field of Albanian studies, who left a significant mark on the Faculty of Philology in Belgrade with his contribution. Dančetović stands out as a linguist, methodologist, critic, and collector of folklore material, due to his great contribution to the research of the Albanian language and culture, as well as his role as an advocate of the reconciliation of two neighbouring nations.Originally from Kosovo and Metohija, Vojislav Dančetović completed his studies in Zagreb, and thanks to Professor Petar Skok, who noticed his talent for languages, he managed to get a job at the Faculty of Philology in Belgrade as a lecturer. In addition to holding volunteer classes in the Albanian language, he transferred his love for this language to his students who formed associations and gather to share their ideas and opinions. The fact that he can be compared to Vuk Stefanović Karadžić in terms of his oeuvre speaks of his importance.Although Vojislav Dančetović had a significant impact on Albanianology and contributed to the unity of two neighbouring peoples, his works today represent a real challenge to find and research, and his passionate commitment to preserving cultural heritage contributed to the spread of understanding and respect for diversity. His role in forming associations and encouraging the exchange of ideas between students of the Albanian language and literature testifies to his efforts to build bridges between communities.
Keywords: : Vojislav Dančetović, Department of Albanian Language and Studies, Faculty of Philology, Albanian language, bibliography.